Unravelling the replication biology of Providence virus in a cell culturebased model system - Jarvie, Rachel Anne (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2020)
There has been an increase in the number of viral outbreaks in the last decade; the majority of these are attributed to insect-human or animal-human transfer. Despite this awareness, there is limited understanding of the replication biology of the viruses causing the outbreaks and there are few model systems that are available to study RNA virus replication and viral persistence. In this study, we describe a Providence (PrV)-based model system to study virus replication biology. PrV is a single-stranded RNA virus that can cross Kingdom boundaries; it is capable of establishing a productive infection in insect and mammalian cell culture and it is also capable of replicating in plants. Only one other virus has been reported to infect a similar host range - the Nodavirus, Flock House virus (FHV). First, we performed a bioinformatic analysis of the PrV genome and validated the tools that were currently available to work with this model system in mammalian cells. Our data indicate that PrV infection of human cervical cancer (HeLa) cells results in the production of p130, p104/p40 and VCAP, albeit at low levels. While PrV replication in insect cells is associated with the Golgi apparatus and secretory vesicles, in HeLa cells, PrV replication is associated with the mitochondria. It is interesting to note that FHV replication factories are located on the outer mitochondrial membrane. In an attempt to study PrV virus replication in vitro, we adapted the BioID system reported by Roux et al. (2012). Here a promiscuous biotin ligase enzyme (BirA) was fused to a protein of interest and the expression of the fusion protein in mammalian cells resulted in the proximitybased biotinylation of proteins associated with the protein of interest. Using p40 as the protein of interest, we studied the fusion protein (BirA-p40) in transiently transfected HeLa cells and in a stable cell line, using western blot analysis and confocal microscopy. We faced challenges comparing the data collected using the two antibody-based detection techniques and the lack of BirA-p40 detection when using western analysis was attributed to the associated of p40 with detergent resistant membranes. BirA-p40 was subsequently expressed using in vitro coupled transcription/translation reactions, in the presence of excess biotin. While BirA-p40 was robustly expressed under these conditions, biotinylation of BirA-p40 was not detected. We attributed this to the conditions used in the experiments and given additional time, we would extend the duration of biotinylation, in vitro. PrV replication in mammalian cells was detectable using confocal microscopy however the levels of fluorescence were relatively low. The knowledge that p40 was associated with detergent resistant membranes led us to question the impact of detergent treatment of live cells on the detection of PrV replication. PrV-infected HeLa cells were treated with detergents with varying biochemical characteristics and the impact of these treatments on the detection of PrV replication were evaluated. We observed that linear and non-ionic detergents, namely NP-40 and Triton X-100, were most effective at enhancing the detection of viral replication in PrV-infected HeLa cells. Our data confirm that detergent treatment results in enhanced detection, and not enhanced PrV replication, in HeLa cells. Using the stable BirA-p40 expressing HeLa cell line, we showed that the protein is associated with membranes in vitro, and that the enhanced expression of BirA-p40 results in the formation of greater volumes of detergent-resistant membranes. In addition, detergent treatment of unfixed PrV-infected HeLa cells revealed the presence of the PrV p40 protein in the nucleoli of the cells. This is the first report of PrV proteins, which are translated in the cytosol of the mammalian cells, occurring in the nucleus. Our study has resulted in a deeper understanding of PrV replication in mammalian cell lines. A 'simple RNA virus' with only three predicted open reading frames has exhibited high levels of complexity within its elegant simplicity. This study has also highlighted the challenges associated with studying RNA virus replication biology in vitro. Looking forward, the identification of detergent-based enhancement for the detection of PrV replication provides the opportunity to perform more targeted PrV replication studies. The PrV-based model system can also be applied to the identification and analysis of potential broad-spectrum antiviral drugs in vitro. The latter application is particularly relevant considering the increase in the number of viral outbreaks over the last decade.
Keywords: Virology -- Research; RNA viruses; Viruses -- Reproduction; Providence virus